Effects of moving lid direction on mixed convection and entropy generation in a cubical cavity with longitudinal triangular fin insertion - Kolsi, Lioua; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal; Naceur, Borjini Mohamad; Ben Assia, Habib (Emerald Group Publishing Ltd, 2017)
Purpose -The main purpose of this work is to arrive at a three-dimensional (3D) numerical solution on mixed convection in a cubic cavity with a longitudinally located triangular fin in different sides. Design/methodology/approach -The 3D governing equations are solved via finite volume technique by writing a code in FORTRAN platform. The governing parameters are chosen as Richardson number, 0.01 <= Ri <= 10 and thermal conductivity ratio 0.01 <= Rc <= 100 for fixed parameters of Pr = 0.7 and Re = 100. Two cases are considered for a lid-driven wall from left to right (V+) and right to left (V -). Findings -It is observed that entropy generation due to heat transfer becomes dominant onto entropy generation because of fluid friction. The most important parameter is the direction of the moving lid, and lower values are obtained when the lid moves from right to left. Originality -The main originality of this work is to arrive at a solution of a 3D problem of mixed convection and entropy generation for lid-driven cavity with conductive triangular fin attachments.
Keywords: Three dimensions; Lid-driven cavity; Mixed convection; Triangular fin